2019
DOI: 10.1186/s13052-019-0744-5
|View full text |Cite
|
Sign up to set email alerts
|

Weight estimation in Paediatrics: how accurate is the Broselow-tape weight estimation in the Nigerian child

Abstract: BackgroundDetermination of weight in children is an important aspect of their assessment. It has a wide range of usefulness including assessing their nutritional status and drug dose calculation. Despite its usefulness, weight estimation in children in certain conditions can be challenging particularly in emergency situations or in children who are severely ill or cannot stand on standard scales. The Broselow Tape which is a validated tape that is used to estimate weight based on length was developed using hei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
1
6
1
1
Order By: Relevance
“…Moreover, the MPE of the Broselow tape method was 1%; and the proportions of children with P10 and P20 was significantly higher than the APLS method. Our results indicated that the consistency of the Broselow tape was better than the APLS, as supported by the literature from other countries ( 1 , 22 , 24 ). Is the result of the present study due to the inclusion of a uniform body shape population?…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Moreover, the MPE of the Broselow tape method was 1%; and the proportions of children with P10 and P20 was significantly higher than the APLS method. Our results indicated that the consistency of the Broselow tape was better than the APLS, as supported by the literature from other countries ( 1 , 22 , 24 ). Is the result of the present study due to the inclusion of a uniform body shape population?…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, this study does not include a uniform body shape population. The proportions of children with P10 using the Broselow tape was the highest in the > 19-kg group; while the proportions of children with P20 was highest in the < 10-kg group, which differed from studies in other countries ( 1 , 22 , 24 ). The present results did not meet the acceptable accuracy of estimation (P20 > 95% and P10 > 70%), as has previously been suggested ( 4 , 27 ).…”
Section: Discussioncontrasting
confidence: 80%
See 3 more Smart Citations